Transcriptome-Wide m6A Methylation in Skin Lesions From Patients With Psoriasis Vulgaris - Wang, Ya-Nan; Jin, Hong-Zhong (Frontiers in Cell and Developmental Biology, 2020)
N6-methyladenosine (m6A) methylation, as the most prevalent internal RNA modification, has been revealed to play critical roles in various biological functions. In this study, we performed m6A transcriptome-wide profiling in three kinds of skin tissue: involved psoriatic skin (PP), uninvolved psoriatic skin (PN), and healthy control skin samples (NN). The findings revealed that transcripts of PP contained the fewest m6A peaks and lowest m6A peak density. The greatest differences of m6A methylation were observed in the PP vs. NN and PP vs. PN comparisons. Intriguingly, in these comparisons, hypermethylated m6A was mainly enriched within the CDSs and 3′UTRs, while hypomethylated m6A was not only enriched within CDSs and 3′UTRs, but also within 5′UTRs. GO and KEGG pathway analyses indicated that hypermethylated transcripts in PP were particularly associated with response-associated terms, cytokine production, and olfactory transduction. Meanwhile, hypomethylated transcripts in PP were mainly associated with development-related processes and the Wnt signaling pathway. In addition, we discovered that 19.3%–48.4% of the differentially expressed transcripts in psoriasis vulgaris were modified by m6A, and that transcripts with lower expression were more preferentially modified by m6A. Moreover, upregulation of gene expression was often accompanied by upregulation of m6A methylation, suggesting a regulatory role of m6A in psoriasis vulgaris gene expression.